2021
DOI: 10.1109/access.2021.3076975
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Bandwidth Improvement of a Planar Antenna Based on Metamaterial-Inspired T-Matching Network

Abstract: In this paper a metamaterial-inspired T-matching network is directly imbedded inside the feedline of a microstrip antenna to realize optimum power transfer between the front-end of an RF wireless transceiver and the antenna. The proposed T-matching network, which is composed of an arrangement of series capacitor, shunt inductor, series capacitor, exhibits left-handed metamaterial characteristics. The matching network is first theoretically modelled to gain insight of its limitations. It was then implemented di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A rigorous study of metamaterial application in microstrip patch antenna designing has been reported in [27]. It has been observed that the metamaterial is quite often used in antenna miniaturization [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], performance improvement of on-chip antennas in THz frequency band [47,48], designing of impedance matching network [49,50], microwave imaging [51], and mutual coupling reduction in MIMO and SAR antennas [52][53][54][55][56][57][58][59][60][61][62]. Some of the examples of antenna performances under the influence of metamaterial have been listed in the table below (Table 1).…”
Section: Application Of Metamaterials In Designing Of Microstrip Patc...mentioning
confidence: 99%
“…A rigorous study of metamaterial application in microstrip patch antenna designing has been reported in [27]. It has been observed that the metamaterial is quite often used in antenna miniaturization [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], performance improvement of on-chip antennas in THz frequency band [47,48], designing of impedance matching network [49,50], microwave imaging [51], and mutual coupling reduction in MIMO and SAR antennas [52][53][54][55][56][57][58][59][60][61][62]. Some of the examples of antenna performances under the influence of metamaterial have been listed in the table below (Table 1).…”
Section: Application Of Metamaterials In Designing Of Microstrip Patc...mentioning
confidence: 99%
“…In this paper, no decoupling design is included, and the element is simulated by the periodic boundary of the HFSS software during the design, which makes the influence of mutual coupling between elements taken into account. However, [14,15] provide good method for future work.…”
Section: Prototype Fabrication and Measurementmentioning
confidence: 99%
“…The designed lens is composed of isotropic but inhomogeneous metamaterials that can provide impedance matching with free space. A few other examples of impedance-matched devices based on electromagnetic metamaterials can be found in [19][20][21]. In conclusion, the interest in impedance-matched GRIN metamaterials is growing in many applications, with an increasing need for general analytical and numerical studies of impedance-matched metamaterial composites.…”
Section: Introductionmentioning
confidence: 97%